Efektivitas Peraturan Pemerintah Nomor 35 Tahun 2021 dan Peraturan Perusahaan terhadap Pemberian Surat Sanksi kepada Pekerja di PT X - Siti Hajati Hoesin; Ayu Aulia Rahmitasari (Jurnal Syntax Admiration, 2023)
This study aims to analyze the effectiveness of these regulations in terms of sanctioning workers in the work environment. The method used in this study is a literature study, in which data are obtained from literature and documents related to the topic under study. Data analysis was carried out using a qualitative approach, namely by analyzing the content of literature and documents related to government regulations and company regulations related to the provision of sanctions letters to workers. The results showed that government regulations and company regulations have an important role in determining the provision of sanctions letters to workers. However, the effectiveness of these regulations in sanctioning workers still needs to be improved. Some factors that affect the effectiveness of these regulations include workers' awareness of the rules, clarity of regulations, and supervision carried out by the company. This study recommends the need for efforts to improve the effectiveness of government regulations and company regulations related to providing sanctions letters to workers, such as increasing workers' awareness of the rules, clarifying regulations, and increasing supervision by companies. Thus, it is expected to create a better working environment and minimize the occurrence of violations of rules in the workplace.